Vulnerabilities, extreme weather and temporal tensions as experienced by construction workers in the Swedish construction sector - Bo Nilsson; Anna Sofia Lundgren; Jenny Lönnroth (PLoS ONE, 2026)
Aim Climate change poses increasing risks to outdoor occupations, including construction work. This study explores how vulnerability is constructed in narratives of manual labour within the Swedish construction sector, particularly under extreme weather conditions. Methods Drawing on 16 qualitative interviews with Swedish construction workers, the study adopts a social constructionist lens to explore how vulnerability is shaped and experienced. Findings The findings identify multiple, intersecting forms of vulnerability—bodily, hierarchical, material, social, and market-driven—exacerbated by climate-related challenges such as high temperatures, heavy rainfall, and strong winds. Crucially, the analysis highlights how extreme weather disrupts temporal rhythms, widening the gap between scheduled work plans and the actual time needed to complete tasks. Conclusion The paper concludes that vulnerability arises not only from direct exposure to adverse weather, but also through indirect social, material, and temporal dynamics inherent in the construction sector and exacerbated by climate change.